ABUNDANCES of Na, Ca, Mg and Al in the ATMOSPHERES of K SUPERGIANTS of the SMALL MAGELLANIC CLOUD - Komarov, N. S.; Zgoniajko, N. S.; Vasilyeva, S. V. (Одеські астрономічні публікації, 2017)
The abundances of chemical elements Na, Ca, Mg and Al of the nine K-supergiants in SMC was investigated by a method of models of atmospheres. With this goal the CCD-spectrograms with high resolution was used. It is shown that all stars have a deficit abundances of iron from -0.40 to -0.97 dex relatively of Sun. The some differences of contents of elements Na, Ca, Mg and Al in atmospheres of stars SMC and our Galaxy relatively of content of iron was found.